Analysis of Green Concept to Enhance Service Quality of Room Division at Royal Tulip Springhill Resort Jimbaran - Alex Maulana; Lien Darlina; I Ketut Suja; Ni Made Rai Sukmawati (Yayasan Sinergi Widya Nusantara, 2022)
Purpose: The purpose of this research was to analyze green concept in the room division at Royal Tulip Springhill Resort Jimbaran and to determine the effect of the green concept on the room division, namely green front office and green housekeeping, on service quality partially and simultaneously. Research methods: Research data were collected through questionnaires and supported by interviews. The analytical methods used are classical assumption test, multiple linear regression analysis, hypothesis testing (t test, F test, and coefficient of determination). Findings: The green concept in the room division, namely green front office and green housekeeping has a significant positive effect on service quality at Royal Tulip Springhill Resort Jimbaran. Implementation: The inclusion of green concepts creates a beautiful environment, good air, and also reduce the use of excess energy.